Measuring Language Teacher Emotion Regulation: Development and Validation of the Language Teacher Emotion Regulation Inventory at Workplace (LTERI) - Heydarnejad, Tahereh; Zareian, Gholamreza; Ghaniabadi, Saeed; Adel, Seyyed Mohammad Reza (Frontiers in Psychology, 2021)
Educational context is a pool of various emotional demands asking for competent teachers who are capable enough to regulate and manage them. The language teacher emotion regulation focuses on the strategies that language teachers implement to regulate their emotions. Considering the paucity of a psychometrically sound instrument in language teacher emotion regulation, this realm has received scant research attention. Thus, the present study was an attempt to develop and validate a conceptually meaningful and psychometrically sound instrument to capture language teacher emotion regulation strategies at workplace. This study is composed of three phases. In the first phase, based on a comprehensive consideration of the existing literature and the results of a semi-structured interview, a six-component model of the language teacher emotion regulation was designed. In the second phase, the results of exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and reliability estimates confirmed the validity and reliability of the instrument. The results of CFA refined the final version of the instrument. The Language Teacher Emotion Regulation Inventory (LTERI) includes 27 items with six dimensions on a 5-point Likert scale. Each dimension assesses a discrete language teacher emotion regulation strategy at workplace: situation selection, situation modification, attention deployment, reappraisal, suppression, and seeking social support. In the third phase, the validated instrument, LTERI was utilized across two different milieus of language teaching in Iran, namely school and university. To do so, an independent samples t-test was applied. As the findings of this phase demonstrated, there is a statistically significant difference between English as a foreign language (EFL) teachers in the two contexts regarding the employed emotion regulation strategies in their professional lives. The implications of the current study can open new perspectives in educational psychology and teacher well-being. Furthermore, the Language Teacher Emotion Regulation Inventory (LTERI) contributes to the field of teacher education by filling the measurement lacuna and advancing quantitative studies in this regard. More significantly, the implications of this study may uncover new prospects for effective teaching and learning, especially during the COVID-19 pandemic, which can provoke various emotional demands for both teachers and learners.